ABC Costing applied to cost management in a hospital unit at Teófilo Otoni - MG (Research, Society and Development, 2022)
The Hospital under analysis is located in Teófilo Otoni – MG. It serves more than 63 cities and assists around 110,000 calls per year. However, has been facing a serious financial crisis since 2015, culminating in lack of payment to its employees and the outbreak of strikes in 2016 and 2019. Therefore, the main goal of this work is to apply the Activity-Based Costing Method (ABC) in gynecology and obstetrics sector of a private hospital affiliated to the Unified Health System (SUS) in the city of Teófilo Otoni - MG. The developed methodology consists of a mixture of information from the literature and the Hospital under analysis. Through the literature, the main activities that occur in the sector, resource drivers and average time that professionals dedicate to each activity in the sector were determined. Already through the Hospital under analysis, cost reports were obtained from the gynecology and obstetrics sector, within the period from January to May 2022, thus observing the types of resources consumed by it. As a result, the total value of resources consumed by the sector was obtained, equivalent to R$258,310.71. Of this amount, 52.11% of resources are consumed by the activity "Preparation and delivery", 16.86% by the activity "Postpartum recovery and newborn care", 16.25% by the activity "Screening", 13.10% by activity “Patient referral to accommodation” and 1.68% for the activity “Reception”. Finally, it is observed that the ABC costing method is a useful tool for managers, given the financial details that it is able to provide.